2006
DOI: 10.1007/s11218-006-9007-6
|View full text |Cite
|
Sign up to set email alerts
|

Social support networks, stress, sense of coherence and academic success of university students with learning disabilities

Abstract: The current study evaluated the extent to which 191 university students with learning disabilities (LD) differed from 190 students without disabilities in terms of their perceived social support, stress and sense of coherence. The study also investigated students' perceptions of their academic success at university as compared with their rating of their struggles and failures. Findings indicated that students with LD perceived themselves as having less social support than did students without LD. Students with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 41 publications
3
35
0
10
Order By: Relevance
“…These findings are consistent with prior research showing that students with LD frequently have lower grade point averages, have more difficulties in the process of adapting to the academic setting, and are more likely to face the possibility of academic probation than students without LD (Fraizer et al, 2007;Heiman, 2006b;Turnbull et al, 2010;Weyandt & DuPaul, 2008). In addition, the present findings support our hypothesis regarding the unique function of academic self-efficacy as an explanatory variable of the academic achievement and adjustment to the academic setting of students in general, both those with and those without LD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with prior research showing that students with LD frequently have lower grade point averages, have more difficulties in the process of adapting to the academic setting, and are more likely to face the possibility of academic probation than students without LD (Fraizer et al, 2007;Heiman, 2006b;Turnbull et al, 2010;Weyandt & DuPaul, 2008). In addition, the present findings support our hypothesis regarding the unique function of academic self-efficacy as an explanatory variable of the academic achievement and adjustment to the academic setting of students in general, both those with and those without LD.…”
Section: Discussionsupporting
confidence: 92%
“…The findings regarding perceived social support of students with LD are, as they were with self-efficacy, inconsistent. Several studies found lower levels of social support among students with LD (Heiman, 2006b), and other studies found social support to be both directly and indirectly related to adjustment and to psychological well-being among students with LD (Murray, Lombardi, Bender & Gerdes, 2013). Students who received strong support from parents and peers had less difficulty disclosing their disabilities and requesting accommodations in their new educational setting (Murray et al, 2013;Yalcin, 2011).…”
Section: Perceived Social Supportmentioning
confidence: 99%
“…The research has demonstrated that the attributional styles of students with SLD, compared to mainstream peers, are generally reflected in lower levels of self-esteem, persistence, motivation, and expectation of future academic success (Gans, Kenny, & Ghany, 2003;Nunez, GonzalezPienda, Gonzalez-Pumariega, Roces, Alvarez, Gonzalez, Cabanach, Valle, & Rodriguez, 2005;Stone & May, 2002). The negative impact for academic success inherent in the documented attributional styles of students with SLD (Heiman, 2006) underscores the critical role that teachers play in reversing such cycles. It is important, therefore, that we understand the attributions made by mainstream teachers regarding students with SLD in their classrooms.…”
Section: Attributions For Students With Specific Learning Difficultiesmentioning
confidence: 99%
“…Students from working class or poor backgrounds are more likely to work full-or part-time when attending college, reducing opportunities to socialize (Heiman and Kariv 2004) and adding pressure to keeping up with college work (Trainin and Swanson 2005). For both students with and without LD, success is partially predicated on finding the balance between work and play (DaDeppo 2009;Heiman 2006). In addition, when attending college, a student's self-image often shifts, influenced by new academic knowledge and exposure to a more diverse peer group (Troiano 2003).…”
Section: Surveying Previous Studiesmentioning
confidence: 99%
“…Although this stance does not entirely disappear, it does give way to being philosophical and practical; philosophical in that it is rationalized as the need for human bonding at another's expense ("Groups tend to define themselves by what they are not"); practical in that he strongly urges the college administration not to permit another student to experience what he did ("The administration has been much, much nicer to me"). While David did maintain difficulties in making friends among peers, he also managed to befriend some students as well as build strong relations with several professors, creating a social network ("People who have actually committed themselves to a cause") involving respect and understanding (Heiman 2006) that served as a coping mechanism (Heiman and Kariv 2004).…”
Section: Self-directed Actions Toward Academic Successmentioning
confidence: 99%